1999
DOI: 10.2169/internalmedicine.38.957
|View full text |Cite
|
Sign up to set email alerts
|

Primary Duodenal MALT Lymphoma.

Abstract: Primary duodenal MALTlymphoma(MALToma) is a very rare neoplasm arising from the mucosa-associated lymphoid tissue of the duodenum.Wereport a 55-year-old womanwith MALTomalocated in the descending duodenum and accompanying Helicobacterpylori infection of the stomach. Weperformed operative resection due to involvement of the papilla of Vater and submucosal tumor infiltration. Despite wide mucosal spreading, postoperative examination revealed only a small amount of MALToma cells infiltrating into the submucosa. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…The pathogenesis of MALT lymphoma in the prostate is suspected to be related to chronic inflammation. MALT lymphoma most frequently arises in the stomach, while duodenal MALT is uncommon with only 16 reported cases [14][15][16]. Duodenal MALT tends to be diagnosed incidentally because the majority of patients complain of epigastric pain or have no specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of MALT lymphoma in the prostate is suspected to be related to chronic inflammation. MALT lymphoma most frequently arises in the stomach, while duodenal MALT is uncommon with only 16 reported cases [14][15][16]. Duodenal MALT tends to be diagnosed incidentally because the majority of patients complain of epigastric pain or have no specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal lymphoma comprises about 10–20% of gastrointestinal lymphomas and only 0.2–0.6% of large bowel malignancies [2]. MALT lymphoma of the small and large intestine is rare [3, 4, 5, 6]. There are case series described from Japan, China, Italy, and Singapore where they had long-term follow-up of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The stomach is, by far, the most frequent site of involvement [1]. A thorough literature search revealed only 16 reported cases of duodenal MALT lymphoma with median age of presentation being 52 years [6][7][8][9][10][11][12][13][14][15][16]. The majority of patients presented either with epigastric pain or had no specific signs or symptoms and were diagnosed incidentally.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori eradication by antibiotic treatment, surgical resection, chemotherapy, and radiation therapy have all been used with variable success rate. Treatment with H. pylori eradication was successful in four reported cases [6,10,11,16], while the lesions in two cases were unaffected [9,15]. Isomoto et al reported unsuccessful treatment by H. pylori eradication while radiotherapy was completely effective [15].…”
Section: Discussionmentioning
confidence: 99%